O direito à convivência familiar e comunitária de crianças e adolescentes em situação de acolhimento institucional no estado da Paraíba: desafios à efetivação a partir das falas dos(as) assistentes sociais - Freitas, Karoline Silva David de (2020)
The present study has as main objective to analyze the effectiveness of the right to the right family and community coexistence of children and adolescents who are in institutional care services in the state of Paraiba, from the perspective of professional social workers. It is an investigative part of a broad research, called “Violation of Rights and social Vulnerability of Children, Adolescents and Families in the State of Paraiba and the coping Policies”, developed by the Study and Research Group on Children, Adolescents and Families Federal University of Paraiba. The right family and community in the Brazilian Federal Constitution of 1988, in the Child and Adolescent Statute of 1990 and other national laws and regulations as fundamental to the development of children and adolescents. It can be understood as the possibility for children and adolescents to remain in the environment to which they belong and preferably with their families, that is: their parents and / or other family members and in the possibility of another family that can accommodate them. For situations in which there is a need to be temporarily removed from their environment and placed in institutional care, compliance with the principles of exceptionality is essential, and family reintegration is prioritized family reintegration, as this a protective measure. In this sense, to analyze the effectiveness of the fundamental right to family and community coexistence in the state of Paraiba, it was an exploratory research in the 31 (thirty-one) host institutions existing in the state during the execution of the research (2017 and early 2018). For data collection, the interview technique was used, through the application of three semi-structured questionnaires, with 31 (thirty-one) managers, 27 (twenty-seven) social workers and 74 (seventy-four) families. However, for this study we stopped to analyze the research carried out with the social workers of the institutions. Initially, a bibliographic search was carried out using books and scientific article from Social Work and from areas that dialogue with the theme. The methodology of this research is based on the historical and dialectical materialism method, has a qualitative and quantitative approach, with the systematization, reading and interpretation of data according to the content analysis technique. The research identified advances in the predominance of the State’s participation in the provision of childcare services for children and historically been managed by non-governmental institutions, of a religious nature, from the perspective of charity and not of law. However, it showed weaknesses of a structural nature as to the lack of basic resources for carrying out activities in the institution’s daily life. In a addition to the need to expand the actions carried out with the community and strengthen the actions with the families so that in fact this protective measure is carried out in compliance with the principle of exceptionality and brevity, giving children the right to live in family and community. This suggests that putting the paradigm proposed by the organization into practice is a procedural challenge, both non-governmental and governmental.